Effects of BPA on right ventricular mechanical dysfunction in patients with inoperable CTEPH – A cardiac magnetic resonance study. Issue 147 (February 2022) - Roller, Fritz C.; Schüssler, Armin; Hasse, Alexander; Kriechbaum, Steffen; Richter, Manuel; Guth, Stefan; Tello, Khodr; Breithecker, Andreas; Liebetrau, Christoph; Hamm, Christian W.; Mayer, Eckhard; Seeger, Werner; et al.
Highlights: Right ventricular function, pulmonary haemodynamics and right ventricular strain values improved significantly after BPA. GLS showed significant correlations with right ventricular function, pulmonary haemodynamics, and remodelling. In the future, non-invasive therapy monitoring and prognosis may be supported by strain assessment. Abstract: Purpose: The aim of this study was to assess effects of balloon pulmonary angioplasty (BPA) on right ventricular (RV) mechanical dysfunction in patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH) via MRI. Method: MRI at 1.5 Tesla and right heart catheterization were performed before and 6 months after BPA in 30 CTEPH patients (mean age 63.4 ± 10.6 years; 17 female). Feature-tracking strain analysis, including global longitudinal (GLS), circumferential (GCS), and radial (GRS) strain, was performed and compared with right ventricular function, myocardial remodelling (assessed by native T1 times), and pulmonary haemodynamics (mean pulmonary arterial pressure and pulmonary vascular resistance). Results: RVEF (35.9% to 48.4%) increased and mPAP (42.1 mmHg to 33.1 mmHg) and PVR (551.8 to 377.7 dyn∙s/cm 5 ) decreased after BPA (all p < 0.0001). Moreover, RV strain increased (GLS −19.9 to −24.0%, p = 0.0003; GCS −9.4 to −11.0%, p = 0.0022; GRS 38.2 to 50.7%, p = 0.001) and septal native area-adjusted T1 time (AA-T1) decreased (1019.4 to 988.7 ms, p < 0.0001). GLS revealed the best correlations with RVEF (before BPA r = -0.75; after BPA r = -0.54), mPAP (r = 0.36; r = 0.52), PVR (r = 0.49; r = 0.48), and AA-T1 (r = 0.44; 0.19). Conclusion: RV mechanical dysfunction, pulmonary haemodynamics, and myocardial remodelling are markedly improved by BPA. Moreover, RV strain values showed good correlations with RV function, pulmonary haemodynamics, and myocardial remodelling. Therefore, strain analysis might provide new insights regarding therapy outcome, monitoring, and prognosis.